Justice In Judges' Decisions On Criminal Cases According To The View Of Progressive Law - Ari Indra David; Maryanto Maryanto (Universitas Islam Sultan Agung, 2021)
This study aims to find out and examine justice in judge decisions in criminal cases according to the view of progressive law. This study uses a normative juridical approach, which is descriptive analysis. The data used is secondary data obtained through literature study, which is then analyzed qualitatively. The results of this study are that justice in judge decisions in criminal cases according to the view of progressive law must be able to provide spiritual enlightenment for litigants, and strengthen social cohesion in social relations. Progressive judges will use the best law in the worst circumstances. A fair decision in the view of progressive law is a decision that is not merely legalistic in nature, does not only fulfill legal formalities, has a vision for the future, and is partial and sensitive to the fate and condition of the nation and state.